Child Protection in Pornography Law in Indonesia - Faizin Sulistio (Universitas Syiah Kuala, 2023)
With the advancement of technology in the form of the internet, pornographic content has become very accessible to every age including children, as a result of which it has an impact on increasing pornography crimes among the community, especially child pornography. One of the factors that causes this is because sometimes the content is on the same web page as adult pornography content. In other countries, child pornography can be punished if a person commits acts such as viewing and possessing content containing child pornography. Unlike the legal arrangements in Indonesia, child pornography can only be punished if a person distributes or lends his child pornography content to others for commercial purposes only, in this case it does not specifically regulate the act of